AN INVESTIGATION INTO STYLISTIC DEVICES IN THE ENGLISH SCRIPT OF OSCAR WINNING FILMS AND THEIR VIETNAMESE EQUIVALENTS - ĐỖ, THỊ BÍCH TRÂM (2016)
Stylistics and stylistics devices, for a long time, have been considered as the fundamental factor in creating the beauty of any literary works. However, they are not fully appreciated in the translation in general, and translation of films’ script in specific. This study is carried out with the aim of giving description of the use and translation procedures for stylistics devices in script of Oscar winning films. Through a careful investigation into simile, metaphor and metonymy– the three most typical stylistic devices which are used commonly and distinctively in the 10 movies’ script, and undoubtedly create the aesthetic effect of these works of motion picture, I truly hope to prove the important role of stylistics and stylistic devices, as well as ways to converting them into Vietnamese equivalents. Finally, based on the findings and results of this study, some implications for the translating, teaching and learning of English – Vietnamese translation will also be suggested.